Small-signal modelling of AC/MTDC hybrid power systems using Multi-Layer Component Connection Method. (December 2020) - Wang, Hao; Hu, Weihao; Zhang, Guozhou; Tang, Yuanhong; Jing, Shi; Chen, Zhe
Abstract: In order to simplify the stability analysis of an AC/MTDC (multi-terminal direct current) power system, this paper presents a Multi-Layer Component Connection Method (MLCCM)-based small signal model for AC/MTDC hybrid power systems. Based on ML-CCM, the system is partitioned as small individual system or components, including generator units, voltage source converter (VSC) units, time delay units, AC network and DC network. The modelling procedure can be 3 steps. First, the individual components are independently modelled. Second, several small individual components are assembled together to build the AC system model based on component interconnection relationship. Third, all AC power systems and DC network model are assembled together to build the whole hybrid power based on the interconnection relationship. There are three features for the MLCCM: (1) these component models can be built individually; (2) their interconnection relationship is a linear algebra matrix; (3) subsystem model can be verified or debugged individually. Due to the three features, the whole hybrid power can be built easily and it is convenient for finding modelling fault and debugging. An AC/DC hybrid system model in MATLAB/Simulink is also built to validate the effectiveness of the MLCCM-based small signal model.